Pendampingan Penyusunan Laporan Keuangan Dengan EFA Pada KPN SMP Negeri 20 Kota Padang - Fitrah Mulyani; Nino Sri Purnama Yanti; Reni Dahar; Dewi Sartika; Yunita Valentina K; Fitria Rahmi; Widi Wulandari; Noverika Ramadhani (LPPM Universitas Dharma Andalas, 2023)
The target of the service is the Public Servant Cooperative (KPN) SMP Negeri 20 Padang which is one of the KPNs in Padang City, this PKM is a continuation of the output of previous community service activities in the form of technical guidance, to ensure that partners are able to apply Excel For Accounting properly and correct, so that they can present financial reports in accordance with the Regulation of the Minister of Cooperatives and SMEs Number 13 of 2015. It is hoped that after this assistance the Treasurer will be able to prepare annual financial reports properly and correctly in accordance with the Minister of Cooperatives and SMEs Regulation No. 13 of 2015 concerning Accounting Guidelines for Savings and Loans by Cooperatives. This activity was carried out in the form of assistance in preparing KPN Financial Reports for SMP Negeri 20 Padang City using Excel For Accounting (EFA) with the prepared modules. This mentoring activity will continue for the preparation of financial reports as of January 31, 2023.